Effect of massage made with aromatherapy oil after mastectomy on acute arm pain and anxiety: a randomized controlled study protocol - Ataseven, Muzeyyen; Sahin Orak, Nuray (International Journal of Clinical Trials, 2023)
Background: This article summarizes the study protocol currently used to evaluate the efficacy of aromatherapy massage for the relief of post-mastectomy anxiety and acute arm pain. Methods: It is a prospective interventional type three-group, randomized controlled, drug-free clinical trial. Eligible patients will be randomly assigned to one of three groups. The population of the study will consist of 90 patients who have undergone simple mastectomy (SM) and modified radical mastectomy (MRM) in the general surgery ward of a training and research hospital in Turkey. After the operation, the arm on the operated side will be massaged with sesame oil in the first group (n=30), sesame-lavender oil in the second group (n=30), and paraffin oil in the third group (n=30). Conclusions: The primary outcome is the level of acute arm pain and the level of state anxiety. The secondary outcome is vital signs and analgesic use status. Trial registration: International standard randomized controlled trial number NCT05658367.